Study Leaf Spring for Punch in Press Tools - Ahmad Zamheri; Azharuddin; Wirda Novarika (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The development of technology in the material sector is currently very fast, it can be seen from the many uses of metal materials, especially in the mass production industry with certain specifications, such as stainless steel, high carbon steel, and tool steel. Home industries such as the manufacture of rings, pans, bottle caps, stove components and others often use these materials as materials to make tools called press tools. In this press tool, high carbon steel or tool steel is mostly used as a punch, but as the cost and difficulty of these materials make home industries suffer big losses for the manufacture of production tools. For this reason, through this study the authors conducted experiments in the laboratory on recycle leaf spring materials. The experiment was carried out in four stages of testing, namely composition test, tensile test, hardness test, and microstructure test. The composition of elements of the recycle leaf spring are 0.6627% Carbon (C), 0.7304% Manganese (Mn), 0.0240% Sulfur (S), 0.0257% Phosphorus (P). The tensile strength of recycle leaf springs is 1332.5 kg/mm2. The hardness is carried out with the Rockwell C hardness test, the result of the test is 52.5 HRC. There are elements of martensitic and austenite in the microstructure test. The results of the laboratory experiments were compared with the data in the literature, so this recycle leaf spring material could be used as a substitute for cutting blades in press tools.